2022
DOI: 10.1371/journal.pone.0264780
|View full text |Cite
|
Sign up to set email alerts
|

Using hyperspectral leaf reflectance to estimate photosynthetic capacity and nitrogen content across eastern cottonwood and hybrid poplar taxa

Abstract: Eastern cottonwood (Populus deltoides W. Bartram ex Marshall) and hybrid poplars are well-known bioenergy crops. With advances in tree breeding, it is increasingly necessary to find economical ways to identify high-performing Populus genotypes that can be planted under different environmental conditions. Photosynthesis and leaf nitrogen content are critical parameters for plant growth, however, measuring them is an expensive and time-consuming process. Instead, these parameters can be quickly estimated from hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 153 publications
0
2
0
Order By: Relevance
“…Concerning the red edge, this spectral region (680-780 nm) proved to be highly sensitive to the chlorophyll content of the vegetation [81,82] and has been used to estimate structural features such as LAI [83,84], or nutritional status such as N concentration (e.g., [85]). Recently, Kyaw et al [86] showed that leaf reflectance of hybrid poplars at 712 nm (i.e., included in the B5 range) was a significant wavelength for predicting nitrogen content per unit leaf area (N area ), even if the observed correlation was weak (R 2 = 0.29 with a LASSO model). This relation was found using 105 leaf sample data of 62 Populus genotypes across seven taxa.…”
Section: S2 Spectral Bands In the Swir And Red Edge Domains Are Requi...mentioning
confidence: 99%
“…Concerning the red edge, this spectral region (680-780 nm) proved to be highly sensitive to the chlorophyll content of the vegetation [81,82] and has been used to estimate structural features such as LAI [83,84], or nutritional status such as N concentration (e.g., [85]). Recently, Kyaw et al [86] showed that leaf reflectance of hybrid poplars at 712 nm (i.e., included in the B5 range) was a significant wavelength for predicting nitrogen content per unit leaf area (N area ), even if the observed correlation was weak (R 2 = 0.29 with a LASSO model). This relation was found using 105 leaf sample data of 62 Populus genotypes across seven taxa.…”
Section: S2 Spectral Bands In the Swir And Red Edge Domains Are Requi...mentioning
confidence: 99%
“…Machine vision and hyperspectral imaging are two nondestructive testing techniques that are widely utilized in many industries, including forestry [ 4 ], agriculture [ 5 ], animal husbandry [ 6 ], and fisheries [ 7 ]. Hyperspectral imaging technology is a technology based on image data in multiple narrow bands.…”
Section: Introductionmentioning
confidence: 99%